2022
DOI: 10.1093/ntr/ntac090
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoking and Risk of SARS-CoV-2 Infection and Disease Severity Among Adults in an Integrated Healthcare System in California

Abstract: Introduction The relationship between cigarette smoking status and SARS-CoV-2 infection and coronavirus disease 2019 (COVID-19) severity is highly debated. We conducted a retrospective cohort study of >2.4 million adults in a large healthcare system to evaluate whether smoking is associated with SARS-CoV-2 infection and disease severity. Methods This retrospective cohort study of 2,427,293 adults in KPNC from 3/5/2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…However, former smokers had higher rates of hospital admission (1·10, 1·03–1·08) and death (1·32, 1·11–1·56). 18 The findings highlight the need for further understanding of the mechanisms by which smoking affects the risk of worse outcomes in patients with COVID-19.…”
Section: Links Between Tobacco Use and Covid-19: Epidemiological Evid...mentioning
confidence: 96%
See 2 more Smart Citations
“…However, former smokers had higher rates of hospital admission (1·10, 1·03–1·08) and death (1·32, 1·11–1·56). 18 The findings highlight the need for further understanding of the mechanisms by which smoking affects the risk of worse outcomes in patients with COVID-19.…”
Section: Links Between Tobacco Use and Covid-19: Epidemiological Evid...mentioning
confidence: 96%
“…Infection rates were also slightly lower in former smokers than in never-smokers (0·96, 0·94–0·99). 18 Despite these few positive studies, as indicated above, our review identified many studies suggesting that smoking was not protective against COVID infection, in addition to many that indicated that it was protective, so the evidence remains conflicting (see appendix pp 3–6 ). It is also important to note that almost all the epidemiological studies were limited to adult participants, which limits our ability to comment on younger populations.…”
Section: Links Between Tobacco Use and Covid-19: Epidemiological Evid...mentioning
confidence: 97%
See 1 more Smart Citation
“…However, the frequency and duration of smoking, or time since quitting tobacco use also influence the increased risk posed by this habit. The long-term damaging effects of smoking have been studied by comparing never-smokers to former [ 204 , 789 , 790 , 791 , 792 ] or ever-smokers (former and current smokers combined) [ 124 , 204 , 793 , 794 , 795 ], which consistently showed more severe outcomes (e.g., hospitalization, ICU admission, MV and death) in the latter groups. However, although current smokers compared to (current) non-smokers seem to be more prone to experience severe symptoms and death [ 123 , 794 , 796 , 797 ], when comparing current smokers to never-smokers, some publications reported increased severity [ 204 , 788 , 796 , 798 ], while others no effect [ 791 , 792 , 799 ], and surprisingly, recent cohort studies found lower rates of severe outcomes [ 789 , 790 ] in the smoker group of the study.…”
Section: Host Factorsmentioning
confidence: 99%
“…The long-term damaging effects of smoking have been studied by comparing never-smokers to former [ 204 , 789 , 790 , 791 , 792 ] or ever-smokers (former and current smokers combined) [ 124 , 204 , 793 , 794 , 795 ], which consistently showed more severe outcomes (e.g., hospitalization, ICU admission, MV and death) in the latter groups. However, although current smokers compared to (current) non-smokers seem to be more prone to experience severe symptoms and death [ 123 , 794 , 796 , 797 ], when comparing current smokers to never-smokers, some publications reported increased severity [ 204 , 788 , 796 , 798 ], while others no effect [ 791 , 792 , 799 ], and surprisingly, recent cohort studies found lower rates of severe outcomes [ 789 , 790 ] in the smoker group of the study. The short-term effects of tobacco use are harder to measure in clinical settings, but ambiguous results on the effect of current smoking behavior on COVID-19 might imply further physiological and immunological effects that differ from the mechanisms responsible for long-lasting damage in the lungs.…”
Section: Host Factorsmentioning
confidence: 99%